Building a theory of change for community development and HIV programming: The impact of social capital, stigma reduction and community-level changes on HIV-related health outcomes for orphans and vulnerable households in Mozambique. Issue 3 (27th May 2019) - Thompson, Gretchen H.; Moret, Whitney
ABSTRACT: USAID-funded programs for orphans and vulnerable children (OVC) provide comprehensive sets of services to improve child and household wellbeing for households affected by HIV. Research suggests that OVC programs enhance household- and child-level resilience to economic, environmental, social, or political shocks, but there is little evidence elucidating the pathways by which intervention components, including economic strengthening and social protection programs, affect these outcomes. This case study uses exploratory qualitative research to generate a causal model for the Community Care Program (CCP) in Mozambique. We used the Most Significant Change methodology to compile mini-case studies and identify primary causal pathways between program components and outcomes. We also used the Community Capitals Framework to explore how CCP affected community-level resilience. Our findings suggest that CCP's multi-component approach generated mutually reinforcing drivers that enhanced child-, household-, and community-level resilience. CCP's effects on stigma reduction, increased social support, and economic status were also vital.